Pembrolizumab and lenvatinib in recurrent ovarian clear cell carcinoma resistant to chemotherapy - Blair McNamara; Stefania Bellone; Cem Demirkiran; Tobias Max Philipp Hartwich; Alessandro D. Santin (Elsevier, 2023)
Background: Treatment of ovarian clear cell carcinoma (CCC) poses many challenges. Effective treatment options for recurrent and metastatic disease remain limited. Case: A 70-year-old woman with recurrent metastatic ovarian CCC experienced durable response to the combination of pembrolizumab, a PD-1 targeting monoclonal antibody and lenvatinib, an oral multikinase inhibitor, after failing standard and experimental treatments. She experienced a 40.1% reduction of target lesions over 26 weeks of therapy. CA-125 trends confirmed serial CT scan findings of shrinking disease burden. She experienced overall mild side effects from the drug combination, and lenvatinib dosage was decreased from 20 to 10 mg/day over her 10 cycles. Conclusion: The combination of pembrolizumab and lenvatinib may represent a new treatment option for chemotherapy-resistant ovarian CCC.